Association of CT Scan Parameters with the Risk of Renal Angiomyolipoma Rupture; a Brief Report - Heidari, Razieh; Ghadamzadeh, Mostafa; Bahardoust, Mansour; Khezrian, Forugh; Moradkhani, Afrooz; Ghadimi, Parmida; Bagheri, Seyed Morteza (Archives of Academic Emergency Medicine, 2022)
Introduction: Rupture of renal angiomyolipoma (AML) is an emergency and life-threatening complication. This study aimed to evaluate the association of computed tomography (CT) scan parameters with the risk of rupture in renal AMLs. Methods: In this retrospective cross-sectional study, patients who were referred to a referral university hospital with diagnosis of AML, between 2007 and 2019, were included. Patients were divided into ruptured and non-ruptured cases based on surgery and CT scan findings and the baseline characteristics as well as CT scan parameters were compared between the two groups. Results: 20 AML patients with the mean age of 39.6 ± 12.5 years were included (75% female). The lesion was ruptured in 8 (40%) patients. The mean size of the lesion was ‎97.0 ± 15.9 mm‎‏ in the ruptured and ‏‎72.0 ± 29.4‎‏ in the non‎-‎ruptured AML ‏‎(‎p ‎= ‎‏0.045). The ‎mean fat density based on non-contrast enhanced CT (NCCT) scan (-‎56.1 ± 16.3 ‎vs ‎-‎‎74.9±24.1; ‏p = ‏‎0.018) and contrast enhanced CT (CECT) scan (-‎20.8 ± 16.9 ‎vs ‎-‎‎50.5 ± 31.7; ‏p ‏= ‏‎0.‎016) was significantly higher in the ruptured cases. Total tumor density based on NCCT scan was significantly greater in the ruptured ‎AMLs ‏(‏‎19.6 ± 25.9 ‎‏ vs‎ ‎-22.7±41.6, p=0.033). Conclusion: It seems that some CT scan parameters such as mean fat density and ‎total tumor density ‏could be used for differentiation between ruptured and non-ruptured AMLs.